Evidence-based consensus for treating incipient enamel caries in adults by non-invasive methods: recommendations by GRADE guideline. Issue 1 (November 2020) - Hayashi, Mikako; Momoi, Yasuko; Fujitani, Morioki; Fukushima, Masayoshi; Imazato, Satoshi; Kitasako, Yuichi; Kubo, Shisei; Nakashima, Shoji; Nikaido, Toru; Shimizu, Akihiko; Sugai, Kenichi; Takahashi, Rena; et al.
Abstract: Remineralization treatment, which offers the advantage of being non-invasive, is increasingly being used as a minimal intervention treatment in managing incipient enamel caries. The aim of this review was to develop EBM guideline for optimized strategies for non-invasive treatment of incipient enamel caries. Japanese Society of Conservative Dentistry (JSCD) guideline committee formulated a Guideline for treating incipient enamel caries using the GRADE system, which is the global, mainstream standard for guideline development. The committee selected the most frequent clinical questions (CQs) in treating incipient enamel caries and identified clinically important outcomes in evaluating the efficacy of treatments. Using extensive electronic and manual searches, relevant randomized controlled trials and controlled clinical trials were identified. Based on evidence profiles produced by the committee, the panel discussed the effects, benefits and disadvantages of the selected treatments, as well as their cost effectiveness and feasibility, in order to achieve a consensus in treating incipient enamel caries non-invasively. A recommendation was made for each clinical question after voting by the panel members. Based on the evidence profile and panel discussions for each CQ, the experts strongly recommended application of topical fluoride to inhibit cavitation of incipient enamel caries, and to diminish white spot lesions.